2015
DOI: 10.1007/s11103-015-0376-0
|View full text |Cite
|
Sign up to set email alerts
|

CEF1/OsMYB103L is involved in GA-mediated regulation of secondary wall biosynthesis in rice

Abstract: Although the main genes in rice involved in the biosynthesis of secondary wall components have been characterized, the molecular mechanism underlying coordinated regulation of genes expression is not clear. In this study, we reported a new rice variety, cef1, showed the culm easily fragile (CEF) without other concomitant phenotypes. The CEF1 gene encodes a MYB family transcription factor OsMYB103L, was cloned based on map-based approach. Bioinformatics analyses indicated that CEF1 belongs to the R2R3-MYB subfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 62 publications
0
59
0
Order By: Relevance
“…OsMYB46 and ZmMYB46 , the orthologues of Arabidopsis MYB46 / MYB83 , share similar functions and are able to activate the secondary wall biosynthetic program when overexpressed in Arabidopsis [14]. CEF1/OsMYB103L and MYB61 are also involved secondary wall biosynthesis mediated by the GA pathway, which can affect leaf shape, cellulose synthesis and mechanical strength in rice [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…OsMYB46 and ZmMYB46 , the orthologues of Arabidopsis MYB46 / MYB83 , share similar functions and are able to activate the secondary wall biosynthetic program when overexpressed in Arabidopsis [14]. CEF1/OsMYB103L and MYB61 are also involved secondary wall biosynthesis mediated by the GA pathway, which can affect leaf shape, cellulose synthesis and mechanical strength in rice [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…AtMYB103 has been suggested as a key gene regulating the expression of ferulate-5-hydroxylase (F5H), which directs lignin biosynthesis towards formation of syringyl-rich lignin (Öhman et al ., 2013) and was initially suggested to regulate lignin composition exclusively. However, MYB103 orthologues of grass species have also been shown to promote cellulose and hemicellulose genes (Hirano et al ., 2013; Yang et al ., 2014; Ye et al ., 2015) and AtMYB103 at least associates with cellulose synthase promoter sequences (Zhong et al ., 2008; Taylor-Teeples et al ., 2015). The predicted MsMYB103 protein shares 43.9% identity and 51.9% similarity on amino acid level with AtMYB103 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that AtMYB103 specifically regulates F5H expression to modulate lignin S:G ratio (Öhman et al ., 2013). However, this direct and specific link could not be established for MYB103 proteins originating from grass species, which were shown to regulate cellulose and hemicellulose (Hirano et al ., 2013; Yang et al ., 2014; Ye et al ., 2015). In line with these results, MsMYB103 seems to orchestrate and finetune SCW formation and lignin biosynthesis more broadly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brittle culm is an important constraint to high-yielding stable rice production. This mutation can lead to a decrease in the mechanical strength of stalks, thereby reducing the lodging resistance of rice [25,26]. In this study, we analysed a brittle culm mutant generated by ion-beam irradiation.…”
Section: Pcr and Hrm Analysis Of Rice Mutants On The Instrumentmentioning
confidence: 99%